Efikasi Guru Mipa SMP dalam Menerapkan Pendekatan Saintifik - Fanani, Zaenal (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2014)
This study is meant to examine the level of efficacy of mathematicsteachers for junior high schools in implementing scientific approach. Italso examines the difference of efficacy of the mathematics teachers ofjunior high school in implementing scientific approach based on genderand teaching experience. The method used in this research is quantitativemethod. The sample size includes 44 junior high school mathematicsteachers, comprising of 17 male teachers and 27 female teachers. Theselected area is Tabalong district, South Kalimantan. Data has beencollected by using a Likert scale instrument (1-4) with 5 items. Respondentsare junior mathematics teacher who attended the LPMP Lesson Study.The results of this study indicate that: (1) as much as 40% of the teacherswere not sure about their ability (low efficacy levels) in implementingthe scientific approach, (2) there is a significant difference in the teacherefficacy between new and senior teachers (p = 0.003 <0.05), and (3) thereis a significant difference in the teacher efficacy between male and femaleteachers (p = 0.007 <0.05).